Livestock monitoring prototype implementation and validation - Aleluia, Vitor M.T. (2023)
This paper presents the proposal, implementation and validation of a low cost fault-tolerant functional prototype for livestock monitoring. This prototype uses IoT devices, ESP8266 and ESP32, creating a mesh network, managed by the painlessMesh library, with WiFi and LoRa technologies. It allows, for instance, the collection of vital signs from animals. In comparison with the traditional method of livestock examination, this cost-efficient approach reduces manual labor and saves working time. It also improves animal health, increases profits and decreases the environmental footprint.